Trapped in domestic violence – narratives of older women - Maćkowicz, Jolanta (Old Age in the Stream of Life: Reflections on Old Age. Volume 2, 2019)
The paper focuses on violence against seniors; a phenomenon that will increase due to the ageing of society. Two autobiographical-narrative interviews are presented – with older women who have experienced long-term domestic violence from their husbands. The goal is to show individual trajectories revealing the biographical struggle with trauma during 40 years of their adult life. Living in violent relationships, both women lived with lowered self-esteem. Long-term, brutal violence evoked very strong, extreme emotions in the narrators, accompanied by suffering, fear and a sense of powerlessness. The analyses show an example of overcoming barriers and a heroic inner fight in the process of dealing with traumatic life experiences.